Stability analysis on reiner-phillippoff hybrid nanofluid flow over a wedge - Iskandar, Waini; Khairum, Hamzah; Najiyah Safwa, Khashi’ie; Nurul Amira, Zainal; Abdul Rahman, Mohd Kasim; Anuar, Mohd Ishak; Pop, Ioan Mihai (Pushpa Publishing House, 2025)
This paper reports on the fluid flow characteristics as well as the heat transfer attribute of a Reiner-Philippoff (RP) fluid past a permeable shrinking wedge with a particular focus on the incorporation of the AA7075-AA7072/methanol hybrid nanofluid. Through the application of suitable transformations, the original model in partial differential equations (PDEs) is converted into ordinary differential equations (ODEs) of a specific form. The ODEs are then solved using the bvp4c solver in MATLAB software. The findings showed that when the magnitude of the magnetic parameter is increased, skin friction and heat transfer rate both are increased. Moreover, the inclusion of hybrid nanoparticles has a positive impact on the system, leading to a 6.16% increment in magnitude of skin friction while boosted about 24% improvement in thermal performance. The confirmation of dual solutions leads to a study of stability analysis to examine the reliability of the first solution. It is important to note that the current findings are novel and original for the study of RP hybrid nanofluid past a permeable shrinking wedge.